Culturally adapted family intervention for schizophrenia in Pakistan: a feasibility study. (1st September 2021) - Husain, Muhammad Omair; Khoso, Ameer B.; Renwick, Laoise; Kiran, Tayyeba; Saeed, Sofiya; Lane, Steven; Naeem, Farooq; Chaudhry, Imran B.; Husain, Nusrat
Abstract: Objectives: To establish feasibility and acceptability of a Culturally adapted Family Intervention (CulFI) that was developed using an empirically derived conceptual framework in Pakistan. Methods: A rater-blind, randomised trial to evaluate the feasibility and acceptability of delivering CulFI compared to treatment as usual in Karachi, Pakistan. Indicators of feasibility included evaluation of recruitment rates, retention and randomisation. We also evaluated the acceptability of the intervention and trial procedures. Results: Excellent recruitment and retention rates informed the feasibility of the intervention. CulFI had more than a 90% participant attendance of 8–10 sessions and retained more than 90% who commenced in the intervention. Eighty percent of those who initially provided consent were willing to be randomised and the quality of CulFI was rated as good to excellent by 85.7% of participants. Conclusions: Importantly, this study determines that pathways into a psychosocial intervention can be established in Pakistan. A combination of factors contribute to low levels of access to psychiatric care including different explanatory models of illness, small numbers of trained staff, limited resources and reliance on traditional healers. These results support the feasibility, acceptability and merit of conducting a full-scale trial of CulFI in comparison with standard care. ClinicalTrials.gov Identifier: NCT02167347 KEY POINTS: The significant treatment gap in LMICs leaves families providing much of the care for people with schizophrenia. There is limited evidence from LMICs supporting the effectiveness and feasibility of psychosocial interventions more broadly, and family interventions specifically. This study adds to the scarce literature and demonstrates that pathways into delivering psychosocial interventions can be established in Pakistan. The results of this trial support the feasibility and acceptability of a Culturally adapted Family Intervention (CulFI) for schizophrenia patients and their families in Pakistan A full-scale trial of CulFI in comparison with standard care is warranted to determine clinical and cost-effectiveness.